DEVELOPMENT OF DIGITAL POSTER SERIES MEDIA FOR CLEAN AND HEALTHY LIVING BEHAVIOR PROMOTION IN HIGH SCHOOL SETTINGS - Budi Kristianto; Budi Prasetyo; Erinda Nur Pratiwi (Jurnal Kesehatan Kusuma Husada, 2026)
Background: The persistent challenge of promoting Clean and Healthy Living Behavior (CHLB) among high school students, along with a critical gap in engaging, contextually relevant digital content for social media, underscores an urgent need for innovative interventions. This study aims to develop and evaluate a digital poster series for CHLB promotion, specifically designed for the Instagram platform.Methods: This Research and Development (R&D) study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants included a purposive sample of 40 high school students from SMA Negeri 1 Simo, Boyolali, comprising 10 students for a small group trial and 30 for a large group trial, selected based on their willingness to participate and school enrollment. Data were collected using quantitative evaluation sheets (5-point Likert scale) and qualitative comment/suggestion forms.Results: The results demonstrated the high feasibility and effectiveness of the digital poster series. Expert validation yielded a 75% score in the first stage, leading to key revisions. Student trials showed overwhelmingly positive quantitative results, with average assessment scores ranging from 4.50 to 4.67 out of 5, translating to feasibility percentages of 90% to 93.33% across all assessed aspects. Qualitative feedback highlighted the media’s visual appeal, modern design, and relatable language, though students suggested increased interactivity.Conclusion: This study successfully developed and evaluated a series of highly feasible and effective digital posters for promoting healthy lifestyles among high school students.